The Greater Chaco Landscape : Ancestors, Scholarship, and Advocacy - Heitman, Carrie C.; Van Dyke, Ruth M.; Project Muse. (Louisville : University Press of Colorado, 2021)
"Since mid-1970s, government agencies, scholars, tribes, and private industries have attempted to navigate conflicts involving energy development, Chacoan archaeological study, and preservation across the San Juan Basin. Examines both the imminent threat by energy extraction and ways of understanding Chaco Canyon--and Chaco-era great houses and associated communities"--
The greater Chaco landscape volume / Ruth M. Van Dyke and Carrie C. Heitman -- Chaco landscapes : a personal account / Stephen H. Lekson -- Landscapes, horticulture, and the early Chacoan Bonito phase / Thomas C. Windes and Carla R. Van West -- Linear cultural alignments in the western San Juan Basin (VIDEO ONLY) / Phillip Tuwaletstiwa and Michael P. Marshall -- Rock art in the Chaco landscape / Dennis Gilpin -- Enigmatic rock features : shrines, herraduras, stone circles, and cairns on the greater Chaco landscape / Ruth M. Van Dyke -- Acoma (Haaku) perspectives (VIDEO ONLY) / Ernest M. Vallo, Jr. -- Dine perspectives (VIDEO ONLY) / William B. Tsosie, Jr., with Denise Yazzie, Eurick Yazzie, and Tristan Joe -- Hopi perspectives (VIDEO ONLY) / Terrance Outah, Georgiana Pongyesva and Ronald Wadsworth -- Zuni perspectives (VIDEO ONLY) / Octavius Seowtewa, Presley Haskie, and Curtis Quam -- Viewscapes and soundscapes / Ruth M. Van Dyke, Timothy De Smet, and R. Kyle Bocinsky -- Night skies (VIDEO ONLY) / G.B. Cornucopia -- New light on Chaco's greater landscapes with emerging technologies / Richard A. Friedman, Anna Sofaer, and Robert S. Weiner -- Geospatial data, remote sensing, and aggregating roads data / Carrie C. Heitman and Sean Field -- The protection of monuments and landscapes in Britain : a historical view / Julian Thomas -- Protecting the greater Chaco landscape : preservation and advocacy / Paul F. Reed -- What can be discovered from Chaco archaeology? / Thomas Lincoln.
Description based on print version record.
Keywords: Pueblo Indians -- Dwellings; Mineral industries; Landscapes; Chaco culture; Chaco architecture; Antiquities; Mineral industries -- New Mexico -- Chaco Canyon; Landscapes -- New Mexico -- Chaco Canyon; Pueblo Indians -- Dwellings -- New Mexico -- Chaco Canyon; Chaco culture -- New Mexico -- Chaco Canyon; Chaco architecture -- New Mexico -- Chaco Canyon; New Mexico -- Chaco Canyon; Chaco Canyon (N.M.) -- Antiquities; Electronic books